Insurtech, Proptech & Fintech Environment: Sustainability, Global Trends and Opportunities - Rambaud, Salvador; Pascual, Joaquín López (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint relating the Insurtech, Proptech, and Fintech environments tries to provide a wide range of perspectives about these sectors, focusing on fields such as financial technology, banking, insurance, real estate, digital implementation, and quantitative analysis, among others. It is beyond any doubt that this sector is probably one of the most relevant and disrupting new markets in recent years, with a great potential to generate collaborations with financial institutions and the insurance world, which jointly grow towards a more innovative business model. The lines between financial services and technology have blurred to the point that the previously distinct sectors are colliding. In effect, digital-only banks are offering redesigned client propositions and cost profiles, and consumers are ready for the digital shake-up. The Special Issue "Insurtech, Proptech, and Fintech Environment: Sustainability, Global Trends and Opportunities" has included original contributions demonstrating significant advancements, innovations, relevance, and potential growth in this sector in the forthcoming years. We have also focused on the main forms of interaction between banks and FinTech companies.